New records of elasmobranchs in the Bay of Bengal, Bangladesh: further taxonomic research is essential - Haque, Alifa Bintha; White, William T.; Cavanagh, Rachel D.; Biswas, Aparna Riti; Hossain, Nazia (Zootaxa, 2021)
To evaluate the species diversity and strengthen the taxonomic identification of elasmobranchs in the Bay of Bengal, Bangladesh, a study was conducted in the southeast coastal region between January 2016 and March 2018. Using morphological and genetic identification techniques, this study presents 22 species from the region. Thirteen of these are new records. The new records consist of eight species from the family Dasyatidae, and one each from Mobulidae, Rhinobatidae, Narcinidae, Hemiscylliidae and Triakidae. Furthermore, four occurrences are first verified reports, and five are potential new records requiring further taxonomic investigation.